Pengaruh Lingkungan Kerja dan Work Life Balance terhadap Kepuasan Kerja Karyawan pada PT Bumi Serpong Damai Tbk Tangerang Selatan - Esteria Silalahi; Nurhadi Nurhadi; Seno Sudarnomo (BADAN PENERBIT STIEPARI PRESS, 2025)
This study was motivated by the importance of work environment and work-life balance in improving employee job satisfaction at PT Bumi Serpong Damai Tbk. The purpose of this study was to examine the partial and simultaneous effects of work environment and work life balance on employee job satisfaction at PT Bumi Serpong Damai Tbk. The population and sample for this study consisted of 100 respondents, with a saturated sampling technique used. The results of the study indicate that the work environment has a positive and significant influence on job satisfaction, with a calculated t-value of 5.038 (p < 0.05). Work life balance also has a positive and significant influence, with a calculated t-value of 5.765 (p < 0.05). Simultaneously, both variables significantly influence employee job satisfaction with a calculated F value of 89.787 (p < 0.05) and a variable contribution of 64.9%. These findings emphasize that both factors are crucial for management to consider in efforts to enhance employee job satisfaction. Based on the research results, it is recommended that companies improve workplace conditions by providing adequate facilities and creating a supportive work environment. In conclusion, enhancing a conducive work environment and implementing effective work-life balance are key factors in improving employee job satisfaction at PT Bumi Serpong Damai Tbk, which will positively impact overall company productivity and performance.